Cost Estimates for Operating a Primary Care Practice Facilitation Program - Culler, Steven D. (American Academy of Family Physicians, 2013)
PURPOSE: Practice facilitation is widely recognized as a promising method for achieving large-scale practice redesign. Little is known, however, about the cost of providing practice facilitation to small primary practices from the prospective of an organization providing facilitation activities. METHODS: We report practice facilitation costs on 19 practices in South Texas that were randomized to receive facilitation activities. The study design assured that each practice received at least 6 practice facilitation visits during the intervention year. We examined only the variable cost associated with practice facilitation activities. Fixed or administrative costs of providing facilitation actives were not captured. All facilitator activities (time, mileage, and materials) were self-reported by the practice facilitators and recorded in spreadsheets. RESULTS: The median total variable cost of all practice facilitation activities from start-up through monitoring, including travel and food, was $9,670 per practice (ranging from $8,050 to $15,682). Median travel and food costs were an additional $2,054 but varied by clinic. Approximately 50% of the total cost is attributable to practice assessment and start-up activities, with another 31% attributable to practice facilitation visits. Sensitivity analysis suggests that a 24-visit practice facilitation protocol increased estimated median total variable costs of all practice facilitation activities only by $5,428, for a total of $15,098. CONCLUSIONS: We found that, depending on the facilitators wages and the intensity of the intervention, the cost of practice facilitation ranges between $9,670 and $15,098 per practice per year and have the potential to be cost-neutral from a societal prospective if practice facilitation results in 2 fewer hospitalizations per practice per year.